Algal biostimulant enhances biomass and nutrient uptake in peach seedlings - Panhong Zou; Yunying Xiao; Yang Wang; Jinrong Zhang; Qian Deng; Zhiyu Li; Lijin Lin; Huashan Lian (European Journal of Horticultural Science)
Abstract Algal biostimulant plays a vital role in modulating nutrient absorption in crops. This study investigated the impact of an algal biostimulant on the nutrient uptake of peach seedlings by spraying different concentrations [0 (control, CK)-, 600 (T1)-, 900 (T2)-, 1200 (T3)- and 1500 (T4)-fold concentrations] of algal biostimulant. Algal biostimulant resulted in a significant increase in the biomass and photosynthetic pigment content of peach seedlings, and got the maximum biomass at the treatment of T2. Compared to CK, the treatment of T2 increased the root and shoot (stem + leaf) biomass by 40.44% and 41.83%, respectively. In addition, algal biostimulant exhibited a positive influence on the concentrations of nitrogen (N), phosphorus (P) and potassium (K) in peach seedlings, and got the maximum at the treatment of T2. Compared to CK, the treatment of T2 increased the concentrations of shoot N, P and K by 21.73%, 55.83% and 41.26%, respectively. Further analysis revealed a quadratic polynomial regression relationship between the fold concentration of algal biostimulant and the investigated traits such as biomass and concentrations of N, P and K. Therefore, algal biostimulant can promote the growth and nutrient uptake in peach seedlings, and its most effective concentration is 900-fold concentration. Significance of this Study What is already known on this subject? Algal biostimulant plays a vital role in providing nutrients to plants, enhancing their nutrient utilization and bolstering their resistance to stress. Meanwhile, algal biostimulant contains plant hormones, such as auxin and cytokinin, which actively stimulate plant growth. However, there remains a paucity of studies investigating their impact on the biomass and nutrient uptake of fruit tree rootstocks. What are the new findings? This study shows that algal biostimulant can promote the growth and nutrient uptake in peach rootstock (wild peach) seedlings, and its most effective concentration is 900-fold concentration. What are the expected impacts on horticulture? Adopting appropriate measures to enhance the biomass and nutrient uptake of rootstocks is crucial for ensuring high-quality fruit production in fruit trees. This study provides the optimal algal biostimulant concentration that can effectively promote the biomass and nutrient uptake of rootstock (wild peach) seedlings.